Characteristics of Drug Poisonings Presenting to the Emergency Department: An Electronic Medical Record Database Analysis - Appendices - Bell, Matthew; Holbrook, Anne; Wallace, Christine; Hanel, Erich; Rigg, Kaitlynn (Canadian Journal of Hospital Pharmacy, 2023)
Background: Drug poisoning, either intentional or non-intentional, is a frequent diagnosis in the Emergency Department, requiring patient management from multiple services. Objectives: To describe the drug poisonings seen in the ED at a large academic urban hospital. Methods: This was a retrospective, descriptive study using data abstracted from the Epic electronic medical record (EMR) system linked to validated CIHI-coded extracts, for 3 years from 2018 through 2020. Patients diagnosed with an acute drug poisoning presenting to the ED were identified by ICD-10 codes and data were collected on demographics, drugs involved, hospital management and in-patient outcomes. Patients diagnosed with an acute drug reaction, inebriations, non-drug or in-hospital poisonings, were excluded. Data were stratified and analyzed by the intent of drug poisoning. Results: 2983 patients, mean age 38.3 years (SD 16.2), 54.7% female, were included, yielding an overall incidence rate of 15.7 drug poisonings/1000 ED visits (8.1 intentional, 6.4 non-intentional and 1.3 unknown intent). The most prevalent drug sources of intentional drug poisonings were antidepressants (26.9%), benzodiazepines (24.9%) and acetaminophen (21.9%) compared to opioids (46.9%) for non-intentional. 716 (24.0%) patients were admitted to acute care services with an in-hospital mortality rate of 1.0%. 111 (9.0%) patients with non-intentional drug poisoning left against medical advice. 772 (25.9%) patients returned to the ED post-discharge with a subsequent drug poisoning. Conclusions: Drug poisonings are a common cause of visits to urban EDs, are rarely fatal but are associated with large hospital resource utilization, with considerable recidivism.
Keywords: drug poisoning; emergency department